Measuring inflation uncertainty in Turkey - Eda Gulsen; Hakan Kara (Central Bank Review (CBR), 2019)
Measuring and monitoring inflation uncertainty is an essential ingredient of monetary policy analysis. This study constructs survey measures of inflation uncertainty for the Turkish economy. Using density and point inflation forecasts in the CBRT Survey of Expectations, we derive various uncertainty measures through standard deviation, entropy, and disagreement among forecasters. Our results suggest that survey-based inflation uncertainty measures are broadly consistent with market-implied indicators of inflation risk. Moreover, we find that an increase in observed inflation is associated with higher inflation uncertainty across all empirical specifications.
Keywords: 330; Inflation uncertainty; Inflation; Survey data; Disagreement; Density forecasts